2008
DOI: 10.1590/s0006-87052008000300026
|View full text |Cite
|
Sign up to set email alerts
|

Densidade, teor de óleo e produtividade de grãos em híbridos de milho

Abstract: Existe grande variabilidade das cultivares de milho quanto à densidade de grãos no mercado brasileiro, mas se conhece pouco sobre seus teores de óleo. Objetivou-se estudar a variabilidade do teor de óleo nos grãos de híbridos de milho e verificar a existência de correlação entre a produtividade, a densidade e o teor de óleo. Desenvolveram-se, na safra 2002/2903, dois experimentos de avaliação de cultivares, em Assis e Adamantina (SP), utilizando o delineamento em blocos ao acaso com 39 híbridos simples e tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
3
4
1
Order By: Relevance
“…starch and its ratio of amylose to amylopectin, protein and oil) and their packing within the kernel (14) . Density levels here are in line with those found by Duarte et al (15,16,17) in various corn hybrids grown in Brazil as well as Moore et al (18,19) in the USA. Matin et al (10) showed that in dry seasons density increased while in rainy seasons it decreased.…”
Section: Resultssupporting
confidence: 92%
“…starch and its ratio of amylose to amylopectin, protein and oil) and their packing within the kernel (14) . Density levels here are in line with those found by Duarte et al (15,16,17) in various corn hybrids grown in Brazil as well as Moore et al (18,19) in the USA. Matin et al (10) showed that in dry seasons density increased while in rainy seasons it decreased.…”
Section: Resultssupporting
confidence: 92%
“…The A2555 hybrid showed higher lipid content when compared with 2B587 and 30F98; Somma was intermediate. This was corroborated by DUARTE et al (2008), who found more oil in A2555 than in 30F98. The highest protein percentage was observed in 2B587 during the starch-protein separation stage (starch tables), when some protein decantation occurred along with starch, hampering its washing.…”
Section: Volumetric Mass Determinationsupporting
confidence: 52%
“…This indicates that the semi-dent kernel appearance and lower volumetric mass are not always related to a lower density grain. The volumetric weight is a combination of grain density and the way grains are arranged in the container, while the method of floating grains provides an idea of the relationship between hard and soft endosperms (DUARTE et al, 2008). Table 2, the 2B587 hybrid, which has a dent appearance, presented the highest protein content (9.06%), while Somma, that is more vitreous, presented the lowest (8.21%).…”
Section: Volumetric Mass Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a gradual and continuous breeding process to increase the GY and their components. The OC in corn kernels is relatively low, generally between 3 and 6%, and most studies indicate that the OC depends more on the plant genotype than on the environment (Duarte et al., 2008; Paes, 2008).…”
Section: Resultsmentioning
confidence: 99%